Can inertial measurement unit sensors evaluate foot kinematics in drop foot patients using functional electrical stimulation? - d'Andrea, Francesca; Taylor, Paul; Yang, Kai; Heller, Ben (Frontiers in Human Neuroscience, 2023)
The accuracy of inertial measurement units (IMUs) in the measurements of foot motion in the sagittal plane have been previously compared against motion capture systems for healthy and impaired participants. Whilst studies analyzing the accuracy of IMUs in the measurement of foot motion in the frontal plane are lacking. Drop foot patients use functional electrical stimulation (FES) to improve walking and reduce the risk of tripping and falling by improving both foot dorsiflexion and inversion-eversion. Therefore, the aim of this study is to evaluate if IMUs are able to estimate foot angles in the frontal and sagittal planes, in order to help understanding the effects of FES on drop foot patients in clinical settings. Two Gait Up sensors were used to estimate foot dorsi-plantar flexion and inversion-eversion angles in thirteen unimpaired participants and nine affected by drop foot while walking six meters in a straight line. Unimpaired participants were asked to walk normally at three self-selected speeds, and to simulate drop foot. Impaired participants walked with and without FES assistance. Foot angles estimated from the IMUs were compared with those measured from a motion capture system using curve RMSE and Bland Altman limits of agreement. Between participants’ groups, overall errors of 7.95° ± 3.98°, -1.12° ± 4.20° and 1.38° ± 5.05° were obtained for dorsi-plantar flexion range of motion, dorsi-plantar flexion at heel strike and inversion-eversion at heel strike, respectively. The between systems comparison in the ability to detect dorsi-plantar flexion and inversion-eversion differences associated with FES use on drop foot patients provided limits of agreement too large for IMUs to be able to accurately detect the changes in foot kinematics following FES intervention. To the best of the authors’ knowledge, this was the first study to evaluate IMU accuracy in the estimation of foot inversion-eversion and to analyze the potential to use IMUs in clinical settings to assess gait for drop foot patients and evaluate the effects of FES. From the results, it is concluded that IMUs do not currently represent an alternative to motion capture to evaluate foot kinematics in drop foot patients using FES.